General aspects of COVID-19 in pregnant and newborn health: A brief review (Research, Society and Development, 2020)
The SARS-CoV-2 infection started in Wuhan / China in December 2019, spreading rapidly across Europe, the United States and Latin America, becoming a pandemic. COVID-19 is an acute disease with symptoms similar to those of a cold and can evolve to symptoms similar to severe pneumonia, its transmission happens through close contact, through droplets of saliva or particles that contain the virus. The present work aims to carry out an integrative literature review containing the main information about the impact of COVID-19 on the health of newborns and pregnant women. In order to develop it, a narrative review of the scientific literature was carried out, through an electronic search in the MEDLINE, SciELO, PubMed and LILACS databases. The WHO has advocated social isolation, however prenatal care should not be suspended during the pandemic period, noting the importance of taking care of yourself and the baby during pregnancy. Preventive measures, especially hygiene, must be adopted during all baby care. Some studies suggest that SARS-CoV-2 transmission from mother to child during pregnancy is unlikely, but that after birth, a newborn can become infected when exposed to an infected person. In addition, there have been some reported adversities, such as premature birth in babies born to mothers who tested positive for SARS-CoV-2. It can be concluded that more studies are needed to elucidate the characteristics of Sars-Cov-2 infection, especially in newborns, while the ideal is to maintain confidence in science and follow the recommendations recommended by WHO.